(untitled) (American Journal of Islam and Society, 2013)
The thesis of this sophisticated book is that the rebirth of an Islamic identity can only be realized through a decisive replication of the Muslim community created through strict adherence to and implementation of the Qur’anic worldview. The specific details provided by AbdulHamid AbuSulayman in his attempt to present this thesis as credible and worthy of merit invariably expose the work as one of synthesis and the lifetime project of an intellectual who is being propelled by his wanderlust for paving the way for the Muslims’ return to the golden age of the Islamic heritage. For instance, he describes this book as his “extended reflection on the Islamic worldview” (p. xv), around which his scholarship and personal experience have revolved. He also cites this reflection as the reason why he has “grappled with … issues” relating to it from his early days and has continued to promote the same line of thought throughout his “writing career that extended half a century” (p. xx). The book is divided into five chapters. In chapter 1, the author discusses the relationship between the Qur’anic worldview and human nature. He bases his argument on the premise that “every cultural system is associated with an underlying worldview which is translated into action by means of a particular ...